O princípio da proporcionalidade como critério de aplicação da pena - Dobrianskyj, Virgínia de Oliveira Rosa (2009)
The Brazilian Penal Law has suffered lots of alterations in its structure, mainly concerning the criterion of prediction and the model of application of the penalties for the committed crimes. The great difficulty, which is the object of this study, is exactly materializing a penal system which comprises the application of the penal law and the protection of the individual guarantees. This would meet the objectives of a Democratic State of Right that regards the proportionality principle as the criterion to predict and apply the penalty by the legislators and judges, as laws are being published to meet the needs of the society more often at present. The penal law is aimed to solve the conflicts between individuals and society, in search of juridical safety and tranquility through the minimal intervention of the public authorities in the citzens freedom. In this way, it should be used only as ultima ratio, when all the other juridical areas are not enough to solve the conflicts arisen in society.So, only the categories of properties that have constitutional importance will be subject to the penal law. Due to the successive alterations of the penal laws in the past years, it is clear that the Brazilian legislator lacks minimal parameters to arrange his legislative activity at the time of the elaboration of the incriminating penal rule, which most of times is disproportionate to the system of laws. The judge will not be able to alter the legislative structure, and will be limitted to apply the penalty according to the parameters indicated by the law. So, the problem of the penal law does not concern its intervention, but how it has to be done. Nevertheless, the principle of proportionality, although it is not expressed in the constitutional text, will serve as parameter to the legislator and judge at the time of elaborating and applying the incriminating penal rule, in search of the realization of justice, giving to each one what they deserve